SISTEM PENDUKUNG KEPUTUSAN UNTUK MENENTUKAN SISWA SIAP BEKERJA PADA SMK NEGERI 2 SUKOREJO PASURUAN MENGUNAKAN METODE PROFILE MATCHING - Dwanoko, Yoyok Seby; Febrianto, Rian (JURNAL TEKNOLOGI INFORMASI: Teori, Konsep, dan Implementasi, 2018)
Vocational High School (SMK) is a school that is prepared to produce graduates who are competent in their fields so that they can enter the workforce directly.The criteria expected from SMK Negeri 2 Sukorejo can determine which students are ready to work, such as national exams, school exams, competency exams, and internships. Based on this, the Decision Support System is needed to determine students who are ready to work.Decision Support Systems for Determining Students Ready to Work can help to determine which students are ready to work at SMK Negeri 2 Sukorejo